Enhancing the Reliability of Photovoltaic Systems in Microgrid at Campus Area - Hanadi; Christian, Hadi; Tomoyahu, Syafril; Faniama, Virara; Pradipta, Justin; Haq, Irsyad N. Haq; Leksono , Edi (Jurnal Otomasi Kontrol dan Instrumentasi, 2024)
This paper assesses the reliability of photovoltaic systems within a microgrid, considering the system's operational mode and monthly data on solar radiation and load demand. The evaluation encompasses various reliability metrics, including microgrid failure rate, interruption duration, system unavailability, EENS, EIR, LOLE, and LOLP, with the objective of minimizing these parameters. The methodologies applied involve the Markov model and artificial intelligence algorithms such as Naive Bayes and Support Vector Machine (SVM). Results indicate that the microgrid exhibits enhanced reliability in an on-grid mode configuration, with a LOLP value of 0.0008. Furthermore, employing machine learning, specifically SVM, for LOLP calculation based on solar radiation yields a more precise value of 0.7245. This study offers valuable insights for policymakers and system designers in determining the optimal configuration for microgrids.